Abstract 232: Endovascular Thrombectomy for Distal Vessel Occlusions in Early vs Extended Time Window - Amol T. Mehta; Christopher M. Kellner; Tomoyoshi Shigematsu; Hazem Shoirah; Michael T. Caton; Thomas J. Oxley; Reade DeLeacy; J. Mocco; Johanna Fifi; Shahram Majidi (Stroke: Vascular and Interventional Neurology, 2023)
Introduction There has been a growing body of literature in recent years suggesting the safety and efficacy of endovascular thrombectomy (EVT) in patients with acute ischemic stroke (AIS) from distal vessel occlusion (DVO). Limited data is available regarding the risks and benefits of EVT in this patient population, especially when comparing the early window (6 hours from LKW) to the extended window (6‐24 hours from LKW). We aim to study this further. Methods We queried our stroke registry, a prospectively maintained database of AIS patients who presented from December 2014 to July 2023, and isolated patients with DVO who underwent EVT. DVO was defined as M2, M3, M4 occlusion, ACA occlusion, and/or PCA occlusion. We then further subdivided this into two groups, patients within the early window, and patients within the extended window. We compared characteristics between these groups using univariate analysis. We additionally performed a multivariable logistic regression analysis adjusted for Alberta Stroke Program Early CT Score (ASPECTS), National Institutes of Health Stroke Scale (NIHSS) score, age, sex, and use of intravenous (IV) thrombolysis to investigate whether or not extended window thrombectomy was associated with worse outcome. Our primary outcomes were modified Rankin Score (mRS) at discharge and at 90 days. Results Total of 290 patients had DVO and underwent EVT. Of these, 214 had all relevant data. 147 (68.7%) underwent EVT in the early window and 67 (31.3%) received EVT in the extended window. Mean age was 72.3 (±14.4). There were more women in the extended window 51.5% vs 44.8% (χ² = 20.57, p‐value < 0.001). No significant difference was observed in the average NIHSS between early (13.7) and extended (13.9) windows (t=‐0.44, p=0.66). Similarly, the median ASPECTS score was comparable between early (9.3) and extended (9.0) windows (t=1.41, p=0.16). As expected, there was a striking difference seen in patients receiving IV thrombolysis between early (54.5%) and extended (4.5%) windows (χ²=48.48, p<0.001). Post‐operative hematoma also was not different between the early (23.8%) and extended (14.9%) windows (χ² = 0.69, p‐value = 0.40). Symptomatic intracerebral hemorrhage (SICH) was only seen in 3.4% of patient in the early window and 2.9% of patients in extended window. No significant difference was found in the mRS at discharge (early: 3.1, extended: 3.4, t=‐0.90, p=0.37) or at 90 days (early: 3.1, extended: 3.5, t=‐1.08, p=0.29). Additionally, in our multivariable logistic regression model, receiving EVT in the extended window didn't significantly affect the discharge mRS (β=0.10, p=0.27) or the 90 day mRS (β=‐0.15, p=0.38). In this model, increasing age, lower ASPECTS score, and higher admission NIHSS predicted a higher discharge mRS, while IV thrombolysis was linked to a lower discharge mRS. Higher admission NIHSS was associated with a higher mRS at both discharge and 90 days. Conclusion In our study, outcome of EVT in the extended time window in patients with DVO was comparable to EVT outcome in early window, with no increased hemorrhagic complications. More studies are required to further understand the risks and benefits of EVT in patients with DVO stroke